A CORRELATION STUDY BETWEEN STUDENTS’ PERCEPTION ON TEACHERS’ PERFORMANCE IN TEACHING ENGLISH AND THEIR ACHIEVEMENT - Imelda Effendi; Samsul Amri; Melda Yeni (J-Shelves of Indragiri (JSI), 2019)
The main purpose of this study is to find out the correlation between the students' perception of teacher's performance and their achievement at eleventh-grade students of SMK N 1 Kempas. The research design is a correlation study and used a simple total sampling technique in determining the sample. The total of the population was 146 students and amount of sample are 70 students. The data were collected by using a questionnaire for students' perceptions and documentation for students' achievement. The indicators of measurement for students' perception are intelligence, behavior, dressing style, friendliness, and authority, body movement, facial expression, vocal intonation, and achievement. Whereas the indicators of students' achievement are a cognitive domain, affective domain, and psychomotor domain. From the analysis of the result, out of 70 students filling the questionnaire, the students’ mean score for students’ perception of teacher's performance at eleventh-grade students of SMK N 1 Kempas was 79.8 at Good level. Whereas the students' mean score for their achievement at eleventh-grade students of SMK N 1 Kempas was 82.1 at a Good level. For the correlation value, the researcher got r coefficient of 0.868, which is classified as a high level. For hypothesis testing, the researcher got rcalculated (0.868) is higher than r table (1%= 0.249 and 5%=0.238). Therefore Ho is rejected and Ha is accepted. It implies there is a significant and positive correlation between students' perception of teachers’ teaching performance and their achievement at eleventh-grade students of SMK N 1 Kempas.